The Influence Of Socialization Factors Introducing Capital Market Investment Among Generation Z (Students And General Only) In Bengkulu City - Erokda Jumi Putri, Jenni (Utami Publisher, 2024)
The aim of this research is to determine the influence of investment knowledge, minimum capital, capital market training and motivation on interest in investing in shares in the capital market. Method The approach used in the research is quantitative research. The data collection technique in this research is by using a survey. The data collection instrument used in this research was a questionnaire. The known results of data collection carried out on students and the general public for the respondent profile were 30 students and 20 general people who became Socialization Members. 54% of respondents are female and 46% of respondents are male. Respondents' ages were between 20 years and 25 years. The majority of respondents are students and general residents in the city of Bengkulu. Students and the general public in the city of Bengkulu have learned about the basic understanding and mechanisms of investing in the capital market, including the principles and benefits. It can be concluded that the results of the analysis show that investment knowledge, capital market training and motivation have a significant positive effect on interest in investing in shares in the capital market, while minimal capital partially has no effect on interest in investing in shares in the capital market.